The Mathematical Connections Of Slow Learner Student: A Case Study In Inclusion Class YBPK, Kediri - Ika Santia; Vivi Kusumaningrum (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The purpose of this research is to identify which aspect of the mathematics connection of inclusion class, especially slow learner student face. The subject of the research is 10 seventh grade slow learner in YBPK Junior High School, Kediri. While the aspect mathematical connection that had been examined was the ability of student in (1) stating relationship between facts, concepts, or mathematics principle; (2) developing mathematical models of the daily life problems; (3) mentioning the concepts which underlie the solution from the given mathematical problems. The technique for data collection was taken from 3 times test, interview, and observation. Then, the researcher used technique triangulation. The data analysis was presented by reducing, pre, sensing and concluding the data. Results show that the slow learner students tend to weak in (1) can’t writing down the reasons; (2) using picture and illustration to show these problems; and (3) developing a mathematical model without right literation.